1998
DOI: 10.1037/0022-3514.75.3.639
|View full text |Cite
|
Sign up to set email alerts
|

Close-call counterfactuals and belief-system defenses: I was not almost wrong but I was almost right.

Abstract: Drawing on samples of professional observers of world politics, this article explores the interrelations among cognitive style, theoretical outlook, and reactions to close-call counterfactuals. Study 1 demonstrated that experts (especially high scorers on a composite measure of need for closure and simplicity) rejected close-call counterfactuals that redirected history when these counterfactuals undermined a preferred framework for understanding the past (the "I-was-not-almost-wrong" defense). Study 2 demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(84 citation statements)
references
References 41 publications
2
79
1
Order By: Relevance
“…Because individuals who seek status may be more likely to attain their goals when they display confidence, over time, the positive reinforcement of this behavior may lead status-seeking individuals to develop habits of thinking and acting confidently, even when their skills cannot justify such confidence (Radzevick & Moore, 2011). This could provide one explanation for why experts update their judgments less often and more slowly than one might expect (Tetlock, 1998;Tetlock, 2005). Like other individuals seeking status advancement through their careers (Wrzesniewski, McCauley, Rozin, & Schwartz, 1997) experts may find it expedient to exhibit overconfidence in their task abilities.…”
Section: Implications For Statusmentioning
confidence: 99%
“…Because individuals who seek status may be more likely to attain their goals when they display confidence, over time, the positive reinforcement of this behavior may lead status-seeking individuals to develop habits of thinking and acting confidently, even when their skills cannot justify such confidence (Radzevick & Moore, 2011). This could provide one explanation for why experts update their judgments less often and more slowly than one might expect (Tetlock, 1998;Tetlock, 2005). Like other individuals seeking status advancement through their careers (Wrzesniewski, McCauley, Rozin, & Schwartz, 1997) experts may find it expedient to exhibit overconfidence in their task abilities.…”
Section: Implications For Statusmentioning
confidence: 99%
“…Previous research has found that experts with a greater need for closure reject counterfactual scenarios that prove their theories wrong while embracing counterfactual scenarios that prove their theories right (Tetlock, 1998), a form of motivated reasoning that is likely to hinder attempts to accurately model uncertainty in the real world.…”
Section: Thinking Stylementioning
confidence: 99%
“…Our argument here applies to how ordinary people make sense of their own life histories, and not necessarily to how professionals make sense of complex causal sequences far removed from their everyday lives. system defense among political experts committed to the theoretical view that certain things had to happen (Tetlock, 1998). However, in the construction of personal life narratives, individuals have wide latitude to choose which events are pivotal (and how to interpret them), making veridicality an elusive notion.…”
mentioning
confidence: 99%